Urban wildlife corridors: Building bridges for wildlife and people - Zellmer, Amanda J.; Goto, Barbara S. (Frontiers in Sustainable Cities, 2022)
Urbanization is rapidly expanding across the globe, leading to increasing threats to wildlife in and around cities. Wildlife corridors are one strategy used to connect fragmented wildlife populations; however, building wildlife corridors in urban areas remains a challenge because of the number of barriers between habitat patches and the extensive number of property owners and stakeholders involved. Successful urban wildlife corridor conservation thus requires a collaborative approach and a cohesive plan that transcends municipal boundaries. Here we demonstrate how urban wildlife corridor conservation can provide a unique opportunity to build bridges not only for wildlife but also among scientists, non-profits, government agencies, and communities. Our case study centers on the conservation of a network of wildlife corridors in one of the world's megacities, Los Angeles, and the positive feedback loop sparked by collaboration between research and non-profit work. We discuss the benefits of and challenges to building complex collaborations for the purpose of strengthening urban resilience and redesigning sustainable cities.